Relation Between Job Attitudes and Attrition: An Exploratory Study on Information Technology (IT) and Information Technology Enabled Services (ITeS) Sector Employees in India - Pandu, A.; Hussain, Mohammed Galib (Prabandhan: Indian Journal of Management, 2012)
Attrition is becoming an area of growing concern in the Information Technology (IT) and Information Technology Enabled Services (ITeS) sector. The purpose of this paper is to investigate Job Attitudes and their relationship with the IT and ITeS employees' attrition in India. 610 samples were chosen by the convenience sampling method through a questionnaire. Data was analyzed by using the chi-square test and correlation analysis. The chi-square test proved the main hypothesis that there is a relationship between job attitudes and attrition. The results were strengthened by the correlation analysis. In the study, six job attitude variables viz. Achievement, Advancement, Recognition, Growth, Responsibility and Reward were considered. It was observed from the data that when the employees have a positive job attitude, then the attrition tendency among the employees is negative. Eventually, a positive attitude could reduce the rate of attrition. All the variables of job attitude were significantly related to attrition. Hence, the compelling conclusion which emerges from the present study is that a positive job attitude leads to retention; whereas a negative job attitude leads to a high rate of attrition among the IT and ITes sector employees in India.